Challenges to Identifying Economic Development Impacts. Issue 1 (February 2023) - Rohlin, Shawn
Researchers investigating causal estimates of economic development programs face many challenges. This commentary highlights three challenges for future researchers to consider. Specifically, the author discusses how important it is to examine distributional changes and not just mean effects. Additionally, the merits of determining migration effects when studying economic development programs to better understand if original residents benefit from the program are discussed. Finally, the author questions how the pandemic will affect economic development research, particularly relating to how labor markets are defined.